2008
DOI: 10.1515/jall.2008.009
|View full text |Cite
|
Sign up to set email alerts
|

The tone system of the Luanyjang dialect of Dinka

Abstract: This paper presents a descriptive analysis of tone in the Luanyjang variety of Dinka, a Nilotic language spoken in Southern Sudan. We show that LuanyjangDinka has four tonemes, High (H), Low (L), Rising (LH) and Falling (HL). We also describe how underlying tone sequences are often substantially modified in utterances by a number of context-sensitive phonological processes such as dissimilatory lowering of High tones. Given our standard autosegmental description, the phonological categories and processes we po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 14 publications
(17 reference statements)
1
20
0
Order By: Relevance
“…It should not come as a surprise, then, that the vowel system is reduced here, from seven to six phonemes -/"/ does not occur as a short vowel. Further details on this centralisation phenomenon can be found in Remijsen & Gilley (2008). As seen from the examples in (10), and also from those in (5), the vowel length distinction has both a lexical and a morphological function; that is there are short stems and long stems, and each of these can appear in a short grade and in long grade.…”
Section: Vowel Lengthmentioning
confidence: 85%
See 1 more Smart Citation
“…It should not come as a surprise, then, that the vowel system is reduced here, from seven to six phonemes -/"/ does not occur as a short vowel. Further details on this centralisation phenomenon can be found in Remijsen & Gilley (2008). As seen from the examples in (10), and also from those in (5), the vowel length distinction has both a lexical and a morphological function; that is there are short stems and long stems, and each of these can appear in a short grade and in long grade.…”
Section: Vowel Lengthmentioning
confidence: 85%
“…We could conceive of this vowel length distinction affecting the association of tones, with more complex tone patterns occurring in syllables (2b), the end of the target syllable is marked by a dot. From Remijsen & Ladd (2008).…”
Section: Tonementioning
confidence: 99%
“…Consequently we took great care to be sure that the forms we report are correct, putting words in different sentence contexts and carrying out instrumental acoustic measurements where necessary, and we are confident that the data can be considered reliable. As noted above, the dialect under study is Luanyjang Dinka, the sound system of which is familiar to us from several studies carried out in conjunction with the work reported here (Remijsen & Gilley 2008, Remijsen & Ladd 2008, Remijsen & Manyang 2009). The data are based on the speech of the third author, but have been checked for consistency with other speakers in Khartoum; for only ten nouns out of the 400 was there any variability.…”
mentioning
confidence: 95%
“…Dinka is of particular phonological interest because of its rich suprasegmental system, which includes independent distinctions of tone, vowel length, and voice quality. The dialect represented here (Luanyjang, part of the Rek dialect cluster) has four tonemes (Remijsen & Ladd 2008), three degrees of vowel length (Remijsen & Gilley 2008), and a two-way distinction of voice quality (breathy vs. modal or creaky) (Remijsen & Manyang 2009); the facts about other dialects (many of which are essentially undocumented) differ in detail but are broadly similar.…”
mentioning
confidence: 99%
See 1 more Smart Citation